Adjuvant treatment in renal cancer - Stec, Rafał; Wcisło, Gabriel; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2008)
Renal cell carcinoma (RCC) is a rather rare malignancy (about 3% of all tumours). According to the most recent National Cancer Register in Poland, 2150 men and 1501 women were diagnosed with renal cancer in 2004. More than 30% of patients who undergo radical nephrectomy may develop distant metastases. Permanent cure can be obtained in 70-90% of patients in TNM stage I, in 55-70% of patients in stage II, in 20-30% of patients in stage III, and in less than 10% in stage IV. The main locations of distant metastases are: retroperitoneal lymph nodes, lung, bone, brain and liver. There is a great need for novel therapy that could be used in an adjuvant setting, especially in patients harbouring risk factors. In the past, several methods of treatment of patients with advanced RCC have been used: radiotherapy, endocrine drugs and immunotherapy. New candidates for adjuvant treatment seem to be such drugs as tyrosine kinase inhibitors, which have been tested in renal clear cell carcinoma. Two of them, sorafenib and sunitinib, are currently approved for clinical use. Another drug worth investigating with potential anticancer activity against RCC seems to be monoclonal antibody G250. Prognostic and predictive factors appear to be crucial at the time of starting such treatment. Among them some well-known factors have already been studied: Ki-67, p53, gelsolin, vimentin, CA IX, CA XII, PTEN, EpCAM. Optimal adjuvant therapy for resected renal carcinoma remains to be defined and the evaluation of adjuvant therapies requires controlled, randomized trials. Until we receive conclusive data from different clinical trials, observation alone remains the standard of care.